Baltimore's Fort McHenry Tunnel ? Introd[u]ction - Axel J. Pollak (Deep Foundations Institute, 1989)
Since the late 1960's the Interstate Division for Baltimore City (IDBC) has been planning and developing the Interstate Highway System for the city to meet regional planning goals. The principal goals are to provide convenient access to the central business district and the port while diverting through traffic away from these congested areas. Interstate Route 95, an eight-lane highway carrying north-south traffic, has headed the city's priority list; during the 1970's its construction proceeded steadily from both east and west towards the harbor. Closing the final 8800-ft (2670-m) gap under the harbor will complete Interstate 95's construction. This final portion, known as the Ft. McHenry Tunnel project, will be built in nine construction contracts. Construction costs of the complete project are expected to exceed $700 million, making it the costliest single project in the Interstate Highway System. Full funding is being provided initially by the Federal Highway Administration (FHWA), and the Maryland Department of Transportation will re-pay the 10 percent local share from toll receipts within the first three years of operation.